Phytoplankton diversity and abundance in Carigara Bay and the coastal waters surrounding Biliran Island during the red tide occurrence of 2015 - Gariando, Joshua N. (2016)
This study aims to determine the phytoplankton abundance and diversity in Carigara Bay and the coastal waters surrounding Biliran during the Harmful Algal Bloom (HAB) in 2015. Horizontal towing was done to collect 50 mL samples for qualitative analysis while bucket method was done to collect 1 L samples for quantitative analysis. The samples collected were positive with Pyrodinium bahamense var. compressum (Pbc), a red-tide-causing dinoflagellate, which was one of the top three dominant species found with an average cell density of 1.9 plus or minus 2.1x10 raised to the power of 3 cells/L in Carigara Bay and 1.3 plus or minus 2.6x10 raised to the power of 3 cells/L in Biliran. Thalassionema sp. had the highest cell density of 7.8 plus or minus 2.1x10 raised to the power of 3 cells/L and 6.3 plus or minus 2.6x10 raised to the power of 3 cells/L in the Biliran and Carigara Bay sampling sites, respectively. A total of 47 species of phytoplankton were observed in Carigara Bay and the coastal waters of Biliran, composed of 3 cyanobacteria, 27 diatoms and 17 dinoflagellates. Total density of phytoplankton in Carigara Bay was 1.6 plus or minus 2.6x10 raised to the power of 4 cells/L and H'= 2.68 while waters surrounding Biliran had 1.4 plus or minus 2.1x10 raised to the power of 4 cells/L and H'= 3.05. Monitoring of all potentially harmful phytoplankton and other phytoplankton species to understand the ecology of these organisms is necessary. The data generated from these kind of studies can be used to create models to predict harmful algal blooms in the future.